Taking personality seriously: The five factor model and public management - Cooper, Christopher A. et al (2013)
This study documents the use of personality assessment in public administration and examines the relationship between personality and job outcomes among public managers. The limitations and problems with the most popular personality assessment framework, the Myers-Briggs Type Indicator, are discussed. The authors then present the five-factor model of personality as an empirically verified, theoretically sound framework that is widely accepted within the field of psychology. Using a survey of public administrators in three states, it is demonstrated that public managers are aware of personality assessment, use it in their jobs, and are generally convinced of its efficacy. The authors also present the results of personality profiles of public managers demonstrating the usefulness of all five domains of the five-factor model of personality for understanding key outcome measures such as job satisfaction and organizational citizenship behaviors. - Reproduced.
Keywords: Public administration